2018
DOI: 10.22460/jiml.v1i3.p279-282
|View full text |Cite
|
Sign up to set email alerts
|

Talk and Write your mathematical Thinking

Abstract: This research is motivated by the low mathematical communication skills of junior high school students in the city of Bandung Regency. This study aims to determine the comparison of the mathematical communication skills of junior high school students in the city of Bandung regency between the learning usingmodels Think Talk Write. The method used in this study is a quasi-experimental method with a pretest-posttest control group design involving two groups and randomly selected classes, at the beginning and end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…This present finding also ties nicely with a previous study by Nasrulloh and Umardiyah (2020), who confirmed the positive impact of the TTW instructional method on students' critical thinking and mathematical communication. This is also consistent with Ishaya et al (2018) and Supandi et al (2018), who uncovered that the learning method with the TTW model affects the achievement of students' mathematical communication ability and mathematical representation. Regarding using the TTW strategy in a writing context, the results of this study confirm the studies of Tamara and Rusfandi (2021) and Setiawan et al (2017), who revealed that using the TTW technique had positive effects on the students' descriptive writing abilities and had a substantial impact on the students' writing abilities.…”
Section: The Efl Students' Think-talk-write Strategies In the Efl Mat...supporting
confidence: 88%
“…This present finding also ties nicely with a previous study by Nasrulloh and Umardiyah (2020), who confirmed the positive impact of the TTW instructional method on students' critical thinking and mathematical communication. This is also consistent with Ishaya et al (2018) and Supandi et al (2018), who uncovered that the learning method with the TTW model affects the achievement of students' mathematical communication ability and mathematical representation. Regarding using the TTW strategy in a writing context, the results of this study confirm the studies of Tamara and Rusfandi (2021) and Setiawan et al (2017), who revealed that using the TTW technique had positive effects on the students' descriptive writing abilities and had a substantial impact on the students' writing abilities.…”
Section: The Efl Students' Think-talk-write Strategies In the Efl Mat...supporting
confidence: 88%